1996
DOI: 10.1161/01.cir.94.11.2800
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol Inhibits Clinical Progression in Patients With Mild Symptoms of Heart Failure

Abstract: Carvedilol, when added to standard therapy, including an ACE inhibitor, reduces clinical progression in patients who are only mildly symptomatic with well-compensated heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
273
0
11

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 562 publications
(292 citation statements)
references
References 24 publications
8
273
0
11
Order By: Relevance
“…However, exercise tolerance has not been consistently improved with carvedilol in clinical trials in heart failure,28, 29, 30 and treatments that have improved symptoms and exercise tolerance have not produced striking effects on cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…However, exercise tolerance has not been consistently improved with carvedilol in clinical trials in heart failure,28, 29, 30 and treatments that have improved symptoms and exercise tolerance have not produced striking effects on cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…All of these drugs have been shown or strongly suggested to improve outcomes in CHF.i-3,9-12,14-1*, 24. [34][35][36][37][38][39][40][41][42][43][44][45] There are other reasons for the superior outcomes at specialized programs: they include the comprehensive preventive nature of the care, based on frequent evaluation and close interaction with specialized experienced staff. 46 This often results in the identification of problems at early stages.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion can be drawn from the results of multicenter studies that showed an improvement of the hemodynamic parameters and reduction of mortality due to the use of drugs that block beta-adrenergic receptors [73][74][75][76][77][78] . Opposite results were obtained with agonists of these receptors [79][80][81] .…”
Section: Neurohormonal Systemmentioning
confidence: 99%